«Mujer y tigre»: Study of the human organism after death - Fierro Villalba, Marcela Lorena (2022)
In this article we will analyze the story «Mujer y tigre», by Ricardo Palma, in which different forms of murder are taken into account: dismemberment, beheading, and hanging. From these types of death, we will describe the biological process that occurs in the human organism after losing life in the hands of one man.